2012
DOI: 10.4012/dmj.2011-155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of denture base resin after disinfection method using reactive oxygen species (ROS)

Abstract: The effects of certain disinfectants on the stability of a polymethyl methacrylate denture base resin were investigated, including those of a novel disinfection method using reactive oxygen species (ROS). The surface roughness and flexural strength were analyzed to assess the effects of the disinfectants on material properties. The following disinfectants were tested: 5% sodium hypochlorite, 70% alcohol, and ROS. Furthermore, the attachment of Candida albicans to the resin surface was investigated. The disinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In contrast, Odagiri et al . found that disinfection of an autopolymerized denture‐base resin with 5% sodium hypochlorite promoted an increase in roughness (Ra 1.04) and the initial attachment of C. albicans when compared to the control (immersion in water, Ra 0.38) . It should be noted, however, that the increase in C. albicans adherence, although significant, was small (<0.5 log 10 c.f.u./mL).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, Odagiri et al . found that disinfection of an autopolymerized denture‐base resin with 5% sodium hypochlorite promoted an increase in roughness (Ra 1.04) and the initial attachment of C. albicans when compared to the control (immersion in water, Ra 0.38) . It should be noted, however, that the increase in C. albicans adherence, although significant, was small (<0.5 log 10 c.f.u./mL).…”
Section: Discussionmentioning
confidence: 93%
“…As in previous investigations on the adherence and biofilm formation of Candida albicans to denture‐base resins, the arithmetic Ra was chosen to represent the surface roughness in the present study …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make ozone an important therapeutic agent in infectious and inflammatory diseases 8. Furthermore, ozone decomposes rapidly to O 2 and OH radicals in water solutions 910…”
Section: Introductionmentioning
confidence: 99%
“…Immersion in 70% ethanol for 15 minutes caused qualitative changes in the acrylic resin surface, as observed by scanning electron microscope. 33 The search for a simple alternative method of disinfection or sterilization of acrylic resin devices is of interest to clinical dentistry because of problems of cross-infection between the laboratory and dental office and the use of nonsterile immediate dentures and surgical guides. 31 In addition, a wide range of potentially pathogenic microorganisms has been found in previously worn dentures.…”
mentioning
confidence: 99%